Empirical evidence of disease activity thresholds used to indicate need for major therapeutic change in US veterans with rheumatoid arthritis - Sauer, Brian C. (Arthritis Res Ther, 2020)
BACKGROUND: A previous analysis of the Veterans Affairs Rheumatoid Arthritis (VARA) registry showed that more than half of the patients with rheumatoid arthritis (RA) did not receive a major therapeutic change (MTC) despite moderate or severe disease activity. We aimed to empirically determine disease activity thresholds associated with a decision by rheumatologists and nurse practitioners to institute a MTC in patients with RA and to report the impact of that change on RA disease activity. METHODS: We analyzed data from the VARA registry between January 1, 2006, and September 30, 2017. Eligible patients had a visit with 3 disease activity measures (DAMs) recorded: Disease Activity Score for 28 joints (DAS28), Clinical Disease Activity Index (CDAI), and Routine Assessment of Patient Index Data 3 (RAPID3). The Youden Index was used to identify disease activity thresholds that best discriminated rheumatologist/nurse practitioner decision to initiate MTC. Clinical outcome was 20% improvement in the American College of Rheumatology criteria (ACR20 response). The effect of MTC on ACR20 response was presented as crude descriptive statistics and evaluated using G-computation for marginal and conditional effects with established disease activity level combined with an empirical threshold from Youden analysis. RESULTS: The study population comprised 1776 patients (12,094 visits: 3077 with MTC, 9017 without MTC). Empirical thresholds (95% bootstrap confidence interval with 1000 replications) for MTC were 4.03 (3.70–4.36) for DAS28, 12.9 (10.4–15.4) for CDAI, and 3.81 (3.32–4.30) for RAPID3. Visits with MTC had increased likelihood of ACR20 response: risk ratios for ACR20 response for visits with MTC vs without MTC ranged 1.2–2.6 across DAMs; risk differences ranged 0.2–14.5%. CONCLUSIONS: MTC was associated with clinical improvement across all DAMs with the greatest change in patients with RA disease activity above the Youden threshold identified in this work. TRIAL REGISTRATION: VARA Registry, https://www.hsrd.research.va.gov/research/abstracts.cfm?Project_ID=2141698764